HUBUNGAN ANTARA KARAKTERISTIK KEPRIBADIAN ORANG TUA TERHADAP SIKAP SOSIAL SISWA DI MTs NURUL WATON DESA SUNGSANG 3 KECAMATAN BANYUASIN II KABUPATEN BANYUASIN - Neni Anggraini; Muhammad Isnaini; Syarnubi Syarnubi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2021)
Some parents in Sungsang 3 Village, Banyuasin II District, Banyuasin Regency speak harshly to their children, because of the factor of living in the sea area, parents scold their children by saying impolite, lack of motivation of parents in doing spiritual activities, the lack of Parents' religious knowledge to children, some parents give authoritarian punishment to their children who make mistakes, the lack of moral education in the family for the child. This research is a descriptive study with a quantitative approach. The research was conducted at MTs Nurul Waton, Sungsang 3 Village, Banyuasin II District, Banyuasin Regency. The population in this study were all students of MTs Nurul Waton Sungsang 3 Village, Banyuasin II District, Banyuasin Regency, totaling 180 students, while the sample used was 64 students obtained through the proportionate stratified random simpling technique (proportional stratified random sample). The data collection techniques used were questionnaires, observation and documentation. The data analysis technique uses the Product Moment correlation technique. From the results of the research that has been done, the data obtained are: 1) The characteristics of the personality of the parents in Sungsang 3 Village Banyuasin Ii District, Banyuasin Regency are included in the low category with an average score of 57.75 or 58, as many as 29 people or 45%. 2) The social attitudes of MTs Nurul Waton students are in the high category with an average score of 78.9 or 79, 24 people or 37%. 3) Based on the results of the significant correlation test, the results of the comparison of r table (0.3198)> r count (-0.267) with a significant level of 10%, it is concluded that there is no significant relationship between the Personality Characteristics of Parents and the Social Attitudes of Students at MTs Nurul Waton Sungsang 3 Village, Banyuasin II District, Banyuasin Regency.